STUDI TENTANG PENGARUH FAKTOR FUNDAMENTAL TERHADAP HARGA SAHAM PERUSAHAAN DI SUBSEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA PERIODE 2019-2023 - Rabiullanis, Icha Merris; Rosalin, Feronika; Faitullah, Faitullah; Furqon, Muhammad (Jurnal Riset Akuntansi dan Bisnis Indonesia STIE Widya Wiwaha, 2024)
Fundamental analysis involves examining financial data and business cycle data related to both internal and external elements, including government legislation, that affect a corporation, interest rates, and inflation. This study aims to find out how important things affect how much money companies make from mining in Indonesia during 2019 to 2020. It also aims to ascertain the impact of the fundamental components ROE and EPS on stock prices, both partially and simultaneously, for mining subsector enterprises that were listed on the Indonesian Stock Exchange between 2019 and 2023. Purposive sampling was used to select 16 companies that were listed on the Indonesia Stock Exchange between 2019 and 2023. This research uses the statistical tool SPSS 23 to collect data. The findings show that the company DSSA had the highest stock price during the period of 2019-2023, while PTBA experienced a continuous increase in ROE throughout the same period, and SMMT showed a consistent rise in EPS from 2019 to 2023. Partial testing revealed that ROE did not significantly affect stock prices, whereas EPS had a significant impact. Moreover, the correlation between ROE and EPS had a significant impact on stock prices, accompanied by a coefficient of determination value of 0.084.